The Effects of Rootone-F Plant Growth Regulators on the Growth of Duabanga mollucana. Blume Cuttings - Supriyanto Supriyanto; Kaka E. Prakasa (Jurnal Silvikultur Tropika, 2011)
Wood shortage supply from natural forest effected the running of wood-based industry. Therefore forestry entrepreneurs began to switch from also growing tree species to fast growing tree species. Duabanga moluccana Blume is one type of native tree in Indonesia who can growing  fast and have good characteristics for industrial raw materials. Multiplication of Duabanga mollucana can be planting by seeds and also by vegetative propagation. Shoot and stem cuttings is one alternative was to obtain plantation in sufficient quantities and in sort time. The addition of plant growth regulators (Rootone - F) was expected to increase the percentage of rooted materials cuttings and the survival percentage.